The Islamic Learning Environment: Between Physical Formalism and The Internalization of Spiritual Values in The Digital Age - Afriani Afriani; Nurul Aini; Samsinar Syarifuddin (Indonesian Journal of Sharia and Islamic Sciences, 2026)
This study conceptualizes the structural tension between physical formalism and the internalization of spiritual values within technology-mediated Islamic learning environments. Utilizing a non-empirical qualitative library research design, foundational principles from classical Islamic educational treatises are synthesized with contemporary scholarship on digital transformation. The analysis reveals that the rapid adoption of learning management systems and high-tech infrastructure frequently leads to administrative compliance, which obscures the hidden curriculum and marginalizes the cultivation of spiritual adab. To resolve this friction, the study proposes a four-dimensional holistic-digital model that harmonizes physical space, adaptive technology, social networks, and a central spiritual core. Positioned within Sufic frameworks of self-purification and divine wisdom, digital media is re-architected from a speculative distraction into a structured instrument for moral development. Educators, families, and institutional networks are framed as co-constructors of a unified moral ecosystem. Ultimately, this research provides a scalable framework for educational stakeholders to realign digital adoption with the authentic spiritual imperatives of Islamic character formation.